Equivalent Nonlinearities for Studying Nonlinear Effects on Sampled OFDM Signals - Guerreiro, João (2017)
In this work we consider nonlinear effects on sampled orthogonal frequency division multiplexing (OFDM) signals and we present a method for obtaining a polynomial function with small degree that can be used to substitute severe nonlinear characteristics (possibly nondifferentiable, as clipping functions), since it leads to signals with essentially the same spectral characteristics. This equivalent nonlinearity is then employed for performance evaluation of clipped OFDM signals, leading to accurate results with both conventional and optimum receivers.